2003
DOI: 10.1053/jhep.2003.50127
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms and the Progression of Liver Fibrosis: A Critical Appraisal

Abstract: Liver fibrosis is a highly dynamic process in which multiple genes interact with environmental factors. Recent human epidemiologic studies have identified possible polymorphisms in a number of candidate genes that influence the progression of liver fibrosis. These genetic factors could explain the broad spectrum of responses to the same etiologic agent found in patients with chronic liver diseases. Polymorphisms in genes encoding immunoregulatory proteins, proinflammatory cytokines, and fibrogenic factors may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
226
0
10

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(240 citation statements)
references
References 115 publications
4
226
0
10
Order By: Relevance
“…119 Given the observation that a number of individuals with chronic HCV infection have excess hepatic iron, 120 some investigators have examined whether possession of these variants is associated with advanced liver disease. The results of these studies have been discrepant, 119,121 with four studies suggesting an association between possession of HFE variants and increased fibrosis or cirrhosis, 80,92,101,109 and the other studies suggesting that there are no associations. Methodological differences may account for these differing observations.…”
Section: Susceptibility To Persistent Hcv Infectionmentioning
confidence: 97%
“…119 Given the observation that a number of individuals with chronic HCV infection have excess hepatic iron, 120 some investigators have examined whether possession of these variants is associated with advanced liver disease. The results of these studies have been discrepant, 119,121 with four studies suggesting an association between possession of HFE variants and increased fibrosis or cirrhosis, 80,92,101,109 and the other studies suggesting that there are no associations. Methodological differences may account for these differing observations.…”
Section: Susceptibility To Persistent Hcv Infectionmentioning
confidence: 97%
“…Studies using models of hepatic fibrosis in transgenic mice have revealed IL-1β and TGF-β1 as key players mediating liver fibrogenesis [69,70]. Huang and colleagues [71] investigated the role of P2X 7 R in a mouse model of liver fibrosis induced by carbon tetrachloride (CCl 4 ), reporting that P2X 7 R inhibition with a competitive antagonist (A438079) prevented collagen deposition and also significantly reduced the expression of alpha-smooth muscle actin (α-SMA) and TGF-β1.…”
Section: Hepatic Fibrosismentioning
confidence: 99%
“…6 Because demographic and environmental factors account for only 17%ϳ30% of fibrosis variability, 7 there is increasing interest in understanding the influence of host genetic factors on liver cirrhosis. 8 Previous studies regarding host genetic factors that are involved in liver fibrosis have been focused on inflammatory and immunoregulatory pathways. Tumor necrosis factor ␣, 9 transforming growth factor ␤1, 10 monocyte chemotactic protein-1, 11 and complement factor V 12 are well-known examples of factors associated with liver fibrosis.…”
mentioning
confidence: 99%